PARTISIPASI PEMUDA DALAM PENGEMBANGAN KAWASAN EKOWISATA DAN IMPLIKASINYA TERHADAP KETAHANAN MASYARAKAT DESA (Studi di Kawasan Ekowisata Gunung Api Purba Nglanggeran, Desa Nglanggeran, Kecamatan Patuk, Kabupaten Gunung Kidul, DIY - Idah Rosida (Jurnal Ketahanan Nasional, 2014)
The youth in Nglanggeran Village actively participated in developing the village potential namely established Nglanggeran Ancient Volcano as ecotourism area. The youth’s participation was embodied in thought, energy, materials, skill and intelligence, and social participation to supported the Nglanggeran Ancient Volcano ecotourism area development. This purpose’s research was to found out how the youth participate in developing Nglanggeran ecotourism area and its implication on village community’s resilience. The research was conducted with hinterview method and field observation with purposive sampling and analyzed with qualitative descriptive method. The implication of ecotourism area development on village community was over the economic, social community, environment preservation, infrastructure establishment, and youth establishment’s resilience at Nglanggeran Village. Therefore the youth’s participation involvement had to be enhanced to hastened the village’s area development.Keywords: Participation, Ecotourism Area, Village’s Community Resilience